EXTERNAL AUDITOR’S RESPONSIBILITY REGARDYING TO GOING CONCERN ASSUMPTION IN HIS/HERS REPORT: CASE OF KURDISTAN REGION/ IRAQ - Noori, Tazhan Muhammad; Rashid, Chnar Abdullah (International Journal of Research -GRANTHAALAYAH, 2017)
This research mainly focused on the external auditors’ responsibilities in Kurdistan regarding the going concern assumption which consider the future financial conditions of the companies. We interviewed two professional individuals in the Directorate of financial supervision office who are auditing both governmental organizations and private sectors in Kurdistan region. Likewise, 4 owners of the companies who have faced bankruptcy risk in Kurdistan have been interviewed as well. Their main job was manufacturing before they have failed. The purpose of this research is to persuade the companies and external auditors that the external auditor can play a significant role in recommending the companies to improve their financial situations.